Characterization of crude proteases from Pseudomonas sp. PD14 isolated from the gut of rabbitfish Siganus guttatus - Armada, Cindy D.
Gut-associated bacteria of fish are known to produce enzymes which aid in digestion and nutrition of the host. The presence and activities of these bacteria in tropical herbivorous fishes like rabbitfish Siganus guttatus are less known. In this study, protease-producing bacterial isolate PD 14, isolated from the distal region of the gut, was characterized and identified through 16S rRNA gene sequence analysis as Pseudomonas sp. (GenBank accession no. KR779515). The culture conditions for maximum protease production by PD14 isolate which involveds the utilization of fish processing wastes as nitrogen source were also optimized as well as the determination of the crude enzyme's biochemical properties. Optimization results showed that the highest protease production was obtained from the viscera flour (1.0% of Japanese halfbreak (Hyporhampus sajori) as nitrogen source with a specific activity of 365.86U mg protein-1. Moreover, the culture conditions leading to maximum growth and protease production were 0.5% maltose as carbon source in pH 8.0, inoculated with 24 hgrown mother culture and incubated for 48 h at 400C with constant shaking. The crude protease from PD14 isolate was found to be optimally active at pH values ranging from 7-11and at temperatures of 20 to 500C. The enzymes exhibited thermostability, retaining 50% activity at 600C and was fairly stable up to pH 11. Considering the high cost of industriaenzyme production, the use of fish processing wastes for microbial production offers a promising future for enzyme biotechnology.